US Military Power and Interests in Asia-Pacific: The Challenges to Human Security and Development - Journal, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Proceedings on the forum "US military power and interests in Asia-Pacific: The challenges to human security and development."
Keywords: US; Military Power; Asia-Pacific; Human Security; Development